PENELITIAN KERUGIAN ENERGI PADA SAMBUNGAN PIPA T 90 - Salimin, Salimin (Teknik Mesin Universitas Halu Oleo, 2017)
The combination and branching flow is a irreversible process in which the irreversibility in technical application will decrease the system erformance.The way to discover the pressure loss at the combination and branching flow is by measuring the head loss and coefficient of loss. The experiment used 4 kinds of pipe with the variation of Reynolds (Re) from 20092 to 155781. The results of the study indicate the meeting flow: Total coefficient of loss , Ktot(12,7mm) = (2,176 – 0,164), tot(19,1mm)=( 2,836 – 0,515), Ktot(25,4mm)= (2,366 – ,472).Ktot38,1mm = (3,892 – 0,508), Total Head Loss HT12,7mm = (0,789 – 0,101)mH2O, HT19,1mm(0,972 – 0,446)mH2O, HT25,4mm = (1,123 – 0,498)mH2O, HT38,1mm = (1,004 – 0,293 )mH2O branching flow; total coefficient loss, Ktot(12,7mm) = (3,982 – 0,734) Ktot(19,1mm) = (6,302 – 1,455) Ktot (25,4mm) = (8,664 – 2,098), Ktot38,1mm = (13,985 – 3,933) . Total Head Loss HT12,7mm= (1,028 – 0,396)mH2O, HT19,1mm = (0,934 – 0,404)mH2O, HT25,4mm = (0,930 – 0,40)mH2O, HT38,1mm = (0,577 – 0,411)mH2OKey words : coefficient of loss, Head Losses, combination and branching flow